Curriculum Planning and Teacher Organizational Commitment as Predictors of Education Quality in Indonesian Public Elementary Schools - Eliyana Eliyana; Bukman Lian; Suherman Suherman (Yayasan Sembilan Pemuda Indonesia, 2027)
Education quality in elementary schools depends on multiple factors, including managerial planning and teacher commitment. This study examined the effects of school curriculum planning and teachers’ organizational commitment on education quality in public elementary schools in Cempaka District, Ogan Komering Ulu Timur Regency, Indonesia. A quantitative correlational design was employed with a sample of 20 teachers selected from ten public elementary schools (two teachers per school). Data were collected through Likert-scale questionnaires, observation, and documentation. Instrument validity was tested using Pearson product-moment correlation, while reliability was assessed using Cronbach’s alpha (α = 0.953 for curriculum planning, α = 0.930 for teacher commitment, α = 0.969 for education quality). Data were analyzed using descriptive statistics, normality and linearity tests, simple regression, and multiple regression. Results indicated that curriculum planning positively and significantly affected education quality (B = 0.350; β = 0.402; t = 3.724; p < 0.001; R² = 0.262). Teachers’ organizational commitment also had a positive and significant effect (B = 0.382; t = 5.174; R² = 0.369). Simultaneously, both variables explained 59.6% of the variance in education quality (R² = 0.596; F = 14.903; p < 0.001). These findings highlight the necessity of integrating systematic curriculum planning with strengthened teacher commitment to improve education quality. The study contributes to educational management literature by demonstrating that quality improvement requires both structural planning and human resource commitment.